Simplified Cyber Security Framework for Educational Institutions - Seshadri, Nagaraja (Global journal of Business and Integral Security, 2024)
In a broad sense, education is the passing of or transmission of knowledge, skills, and character traits. The education sector can be described as the collection of organizations that provides products and services aimed at enhancing the quality of education in society and includes schools, colleges, and universities and various private institutions like vocational training institutes and coaching institutes. In its entirety, the sector is responsible for training individuals irrespective of their age on new skills, enabling them to obtain meaningful employment, and thus helping accelerate the economic growth. The institutes face many challenges like containing costs, competition for students, differing views on standardized learning, and adapting to changing economic needs. Forming education partnerships, developing customized and personalized learning programs, and adapting to new technologies are some unique strategies institutions adopt to overcome these challenges. With online education gaining ground, educational institutes are easy targets for hackers. In fact, reports of instances of breaches in schools and colleges are increasing year on year. These breaches are more worrying because student safety is compromised as educational institutions are entrusted with data of their students and are responsible for their safety and security. A weak cybersecurity infrastructure can make these people vulnerable and put them at risk. With a proactive approach, it is the right time for them to prioritize security as a focal issue and find a solution for it. Hence, it is important for the institutes to do everything they possibly can to ensure their IT infrastructure including the applications and systems are protected, and work to overcome any cybersecurity challenges. While various cybersecurity controls are adopted by the educational institutes, there is a need to establish a simple, cost-effective framework specific to this sector. This research is an attempt to shed light on the current state of cybersecurity in the higher education sector and study the problems and challenges they are facing in implementing an effective security system. Based on the inputs from the survey and interviews, EduSec framework is recommended as the probable solution to the cybersecurity needs of the educational institutions.